The Anti-Inflammatory Effects of the Methanolic Extract and Fractions from Davilla elliptica St. Hil. (Dilleniaceae) on Bothrops jararaca Envenomation - Nishijima, Catarine Massucato; Delella, Flavia Karina; Rodrigues, Clenilson Martins; Rinaldo, Daniel; Valdyrce, Monica; Lopes-Ferreira, Anjos; da Rocha, Lucia; Anjos Lopes-Ferreira, Monica Valdyrce dos; Lopes-Ferreira, Monica; Machado da Rocha, Lucia Regina; Lucia, Regina; Da Rocha, Machado; et al. (International Journal of Molecular Sciences, 2015)
Inflammation and haemorrhage are the main characteristics of tissue injury in botropic envenomation. Although some studies have shown that anti-venom prevents systemic reactions, it is not efficient in preventing tissue injury at the site of the bite. Therefore, this work was undertaken to investigate the anti-inflammatory effects of the methanolic extract and fractions from D. elliptica and to evaluate the role of matrix metalloproteinases (MMPs) in this process. Effects of the extract and fractions from D. elliptica were evaluated using a carrageenan-induced paw oedema model in rats, and leukocyte rolling was visualized by intravital. The quantification of MMPs activities (MMP-2 and MMP-9) extracted from the dermis of mice treated with extract and fractions alone or incubated with venom was determined by zymographic analyses. Our results show that intraperitoneal (i.p.) injection of fractions significantly reduced paw oedema after the carrageenan challenge. Treatment with the tannins fraction also resulted in considerable inhibition of the rolling of leukocytes and this fraction was able to decrease the activation of MMP-9. These results confirmed the anti-inflammatory activity of the methanolic extract and tannins fraction of D. elliptica and showed that the dermonecrosis properties of B. jararaca venom might be mediated through the inhibition of MMP-9 activity. ; Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP) ; Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq)